Importance of Chemistry in Everyday Life (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article provides a comprehensive overview of the importance of chemistry in everyday life. It highlights the various applications of chemistry in different fields and explains how chemistry affects our daily routines and the world around us. The article covers a wide range of areas where chemistry plays a crucial role, such as the production of soaps and detergents, the development of drugs and cosmetics, energy production and storage, water treatment, materials development, environmental monitoring, forensic science, consumer products, and agriculture. It also emphasizes the contributions of chemistry to environmental protection and sustainability through practices like green chemistry.